VIOLENCE AS SEEN IN BUCHI EMECHETA’S THE BRIDE PRICE - Osée, MUKASEREKA KHIKENZA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Among the plagues surrounding the world today, the most crucial is Gender – based violence. Women and girls are subject of many atrocities, physically, morally and psychologically. Women’s body has become a weapon in battlefield. Women are wildly violated by all kinds of categories of men in society: soldiers, Statesmen, businessmen, etc… Teenagers are savagely violated and sometimes bear undesirable pregnancies which lead either to fistula or death during the birthday. Buchi Emecheta, the author of “The Bride Price” is against the practices of girls’ kidnapping and a forced marriage in African society.